Pengaruh Karakteristik Agregat Terhadap Kuat Tekan Beton Mutu Tinggi - Amir, Andi Ahdan; Parung, Herman; Djamaluddin, Rudy (Jurusan Teknik Sipil Universitas Bangka Belitung, 2023)
The aggregate's quality, geology, geography, climatic conditions, and the technique used to manufacture aggregate all have an effect on the quality of high-strength concrete. In this study, the characteristics of the fine and coarse aggregate from the three sources the Jeneberang, Maros, and Pangkajene rivers—were examined, as well as their effects on the compressive strength of high-strength concrete. The research was conducted in stages, which included the testing of coarse and fine aggregate characteristics, composition of concrete, creat of concrete specimens, compressive strength test, and analysis of aggregate characteristics effect on the compressive strength of high-strength concrete. The results showed that that the fine aggregate characteristics of the Jeneberang River as a whole are better than those of the Maros River and Pangkajene River. While the coarse aggregate properties of the main Lekopancing River are greater than the coarse aggregate characteristics of the Pangkajene River and Jeneberang River. The compressive strength varies based on the fine and coarse aggregates used. Results of the linear regression study of the correlation of aggregate features to fine aggregate compressive strength showed a considerable influence contribution; Organic content 99.6%, water content 86.7%, specific gravity 98.2%, volume weight 98%, absorption 98.8%, and fine modulus 90.3%. Sludge content has an approximate 7% impact. Similarly, the coarse aggregate of parameters showed effect: wear 99.8%, water content 99.8%, specific gravity 99.2%, volume weight 92.6%, and absorption 76.2%, with exception of sludge content, which is only 33.2% 33.2%, and fine modulus 29.8%.